2015
DOI: 10.1111/mmi.13112
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine scanning reveals minor local rearrangements of the horizontal helix of respiratory complex I

Abstract: SummaryThe NADH:ubiquinone oxidoreductase, respiratory complex I, couples electron transfer from NADH to ubiquinone with the translocation of protons across the membrane. The complex consists of a peripheral arm catalyzing the redox reaction and a membrane arm catalyzing proton translocation. The membrane arm is almost completely aligned by a 110 Å unique horizontal helix that is discussed to transmit conformational changes induced by the redox reaction in a piston-like movement to the membrane arm driving pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…We have recently provided evidence (Zhu and Vik 2015), through a cross-linking approach, that the lateral helix in the E. coli Complex I does not play a dynamic role in function. The results of others (Belevich et al 2011; Steimle et al 2015) also support that conclusion. Similarly, the results of the cross-linking approach presented in this report, suggest that the C-terminal extension of subunit K does not play a dynamic role in energy transduction or proton translocation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We have recently provided evidence (Zhu and Vik 2015), through a cross-linking approach, that the lateral helix in the E. coli Complex I does not play a dynamic role in function. The results of others (Belevich et al 2011; Steimle et al 2015) also support that conclusion. Similarly, the results of the cross-linking approach presented in this report, suggest that the C-terminal extension of subunit K does not play a dynamic role in energy transduction or proton translocation.…”
Section: Discussionsupporting
confidence: 69%
“…Subunit L differs from the related subunits M and N in that it has 2 additional TM (transmembrane) helices, which are connected by a long lateral helix that contacts subunits M, N and K (Efremov and Sazanov 2011). The role of the lateral helix has been tested by mutagenesis in several recent studies (Belevich et al 2011; Steimle et al 2011; Steimle et al 2015; Steimle et al 2012; Torres-Bacete et al 2011). Proton translocation likely occurs through four pathways.…”
Section: Introductionmentioning
confidence: 99%
“…When subtracting the spectra before and after addition of NADH, differences of 15–18 cm −1 for the signals of the label visualize experimentally a reorganization of distinct positions within the helix toward a more hydrophobic environment. Previous EPR and fluorescence spectroscopy studies by Steimle et al pointed to a nearly imperceptible movement of the helix upon reduction by NADH.…”
Section: Discussionmentioning
confidence: 97%
“…The movement of the helix was probed with fluorescence and nitroxide labels. Slight conformational changes of the helix during the reduction of the complex by NADH became evident but not a large rearrangement [20]. However, it is possible that the size of the fluorophore and the nitroxide label influenced the conformational flexibility of the helix.…”
mentioning
confidence: 99%
“…1). Cross-linking studies [6], and the results of several other approaches [711], have indicated that this helical element is likely to have a structural role, rather than a dynamic role in proton translocation. Apart from this extra structural component of subunit L, each of these three subunits consists of 14 α-helical TM spans.…”
Section: Introductionmentioning
confidence: 99%